Penicillinase-based amperometric biosensor for penicillin G - Goncalves, Luis Moreira; Callera, Welder F. A. [UNESP]; Sotomayor, Maria Del Pilar Taboada [UNESP]; Bueno, Paulo Roberto [UNESP] (Elsevier B.V., 2014)
A biosensor for penicillin G was created by immobilizing penicillinase to a gold electrode by means of a cysteine self-assembled monolayer. The biosensor amperometrically monitored the catalytic hydrolysis of penicillin in a very sensible manner. Furthermore, it was successfully used to measure the Michaelis-Menten enzymatic constant and a low limit of detection of 4.5 nM was obtained. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Cysteine; Metallo-beta-lactamase; Self-assembled monolayer (SAM); beta-Lactam antibiotic; Lineweaver-Burk plot